(3GdeTGQY hGdeWGQMGJs - (3jMji Hf qMnHT Hf CejQc, CHh GdaJhM, TgGH GdOjf, GdSgQhQOj,J (B587 (3g` s
(3ChdgG (B:s
(3gPG cJGH jTJed Ydi hCQhOJ ajg eHGMK hafhf s
(3BNQgG (B:s
(3hGdZGdHhf GdeNdUhf GdeHjYhf dge HGdUOb s
(3GdfSNI HgG MhGTs
(3fSNI QGHYIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B140 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B189s
Keywords: (3GdadSaI hGdefWbs